A non-Fourier heat flux approach to model MHD Oldroyd-B fluid flow due to bidirectional stretching surface. (October 2017) - Hina, S.; Munir, Maimoona; Mustafa, M.
Highlights: A non-Fourier heat flux approach to model the flow of MHD Oldroyd-B fluid. Flow is created due to stretching of an infinite plane surface in two lateral directions. Homtopy analysis method (HAM) is employed in finding the convergent series solutions. Graphical abstract: Analytical approximations for flow of Oldroyd-B fluid due to bi-directional stretching surface utilizing non-Fourier heat flux model. Abstract: Prime focus of this research is to address the MHD Oldroyd-B fluid flow and heat transfer due to stretching of plane elastic surface in two lateral directions. The phenomenon of heat transfer is modeled under a non-Fourier heat flux theory featuring thermal relaxation effects. Flow field is subjected to uniform vertical magnetic field. Furthermore, fluid with variable thermal conductivity is considered. Appropriate transformations are applied to yield the similar form of governing equations . A powerful analytical approach namely Homotopy Analysis Method (HAM) is opted to develop series solutions involving exponentially decaying functions. The results show that flow fields are appreciably affected with the variation in embedded parameters, especially with fluid relaxation and retardation times. It is found that the structure of solutions depends on a parameter measuring the ratio of stretching rates. Thermal penetration depth decreases for increasing values of thermal relaxation time. Thermal relaxation time has an effective role in improving the cooling process of the stretching surface which is vital in some industrial processes.